"A língua que eu emprestei": variações do PB entre os Macuxi - Martins Filho, José Vilson (2015)
The objective of this focused on the study of Portuguese used, in the written form, by students of the Indian Center of Training and Culture Raposa Serra do Sol in Barro community - Surumu, Roraima state. In visits to the community and listening to expressions like: the chair, the table, my garden, some people. It was proposed as a problem of the research to verify that these variations occurred in writing, as a variation of PB. The theoretical part called Sociolinguistics based this work, from the main external and internal.The study was conducted through literature, qualitativequantitative and field research. In the field research, a questionnaire was applied containing 23 questions with 24 informants, which resulted in the definition of a sociolinguistic profile with predominance of bilingualism L1 (Portuguese) and L2 (Makushi). Were also analyzed 23 stories written by these students, whose results showed of syntactic type, morphological and phonetic. The results recognized linguistic variables in written Portuguese-Makushi, similar to many Rural Portuguese. The study ended with indications of a Portuguese-Makushi as a variant of Portuguese-Brazilian.